Geological significance of delineating paleochannels with AEM. Issue 1 (2nd January 2020) - Chandra, Subash; Choudhury, Joy; Maurya, Pradip K.; Ahmed, Shakeel; Auken, Esben; Verma, Saurabh K.
ABSTRACT: Paleochannels typically act as pathways for groundwater movement and provide a potential source of groundwater. Their presence can be helpful in identifying areas suitable for recharge and at times in mitigating contamination problems in afflicted regions. Thus, mapping of paleochannels is significant in the planning and management of groundwater resources. An airborne electromagnetic (AEM) system employing dual pulse moments has been used extensively for this purpose in India. This paper presents the results over paleochannels defined in three different terranes. In northwest India, a 100 m wide by 80 m deep paleochannel within alluvium overlaying a Proterozoic basement illustrates the impact of neotectonic disturbances in changing the river course. In northeast India's Ganga Plains, a paleochannel is mapped that provides insight into managing groundwater resources of areas polluted with arsenic. In south India, a paleochannel buried under ∼ 100 m thick sequence of coastal sediments is imaged with implications on submarine groundwater discharge.